2011
DOI: 10.1177/1470320311405557
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in ACE2 is associated with a lower risk for fatal cardiovascular events in females: the MORGAM project

Abstract: Angiotensin II, a vasoconstrictor and the main effector molecule of the renin-angiotensin system, is known to influence inflammation, thrombosis, low-density lipoprotein oxidation and growth factors, all of which contribute to cardiovascular disease. The associations of polymorphisms in the angiotensin-converting enzyme 2 (ACE2) gene with cardiovascular risk have not been fully determined. Single nucleotide polymorphisms (SNPs) in ACE2 were genotyped in participants of the prospective MORGAM study (n = 5092) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
(42 reference statements)
2
15
0
Order By: Relevance
“…It’s well known that there is a common genetic basis for dyslipidemia and ASCVD [ 8 ]. Our results showed that 2 SNPs (rs2285666 and rs4646142) was not associated with T2D (see Additional file 1 : Table S4) but exhibited association with T2D with moderate risk of atherogenic dyslipidemia (see Additional file 1 : Table S6, S7), which were consistent with previously reported association of the loci with ASCVD (e.g., coronary heart disease [ 32 ], ischemic stroke [ 33 ]) in T2D patients as well as cardiovascular death in European females [ 34 ]. Similar effects also existed in between rs10911021 and CAD in T2D [ 35 ] as well as between CLOCK polymorphism and stroke in T2D patients [ 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…It’s well known that there is a common genetic basis for dyslipidemia and ASCVD [ 8 ]. Our results showed that 2 SNPs (rs2285666 and rs4646142) was not associated with T2D (see Additional file 1 : Table S4) but exhibited association with T2D with moderate risk of atherogenic dyslipidemia (see Additional file 1 : Table S6, S7), which were consistent with previously reported association of the loci with ASCVD (e.g., coronary heart disease [ 32 ], ischemic stroke [ 33 ]) in T2D patients as well as cardiovascular death in European females [ 34 ]. Similar effects also existed in between rs10911021 and CAD in T2D [ 35 ] as well as between CLOCK polymorphism and stroke in T2D patients [ 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, because administration of losartan normalized blood pressures of ACE2-deficient HF-fed females, these results suggest that ACE2 deficiency augments obesity-hypertension in male and female mice by increasing the AngII/Ang-(1–7) balance. Recent results demonstrated that a polymorphism in the ACE2 gene is associated with a lower risk for fatal cardiovascular events in females 29 , potentially related to 2 alleles of the X-linked ACE2 gene in females compared with males. It is unclear whether gene dosage differences in ACE2 expression between male and female mice in this study contributed to resistance to obesity-hypertension in females.…”
Section: Discussionmentioning
confidence: 99%
“…Another ACE2 polymorphism (rs2285666) was associated with the risk of cardiovascular death in women. 30 On the other side, no man in our study with C genotype in rs4646174 had a positive history of MI. ACE2 exerts cardioprotective effects by preserving jeopardised cardiomyocytes in the border ischaemic zone following experimental MI in rats.…”
Section: Discussionmentioning
confidence: 94%